Mitochondria: a key regulator of programmed cell death in OP - Wang, Kexin; Wang, Zhandong; Ma, Chunhua; Yang, Junfang; Xing, Shangman; Song, Bing; Guo, Chao; Song, Wenjing; Cao, Tingting; Bai, Min; Wang, Yongfeng (Frontiers in Endocrinology, 2025)
Osteoporosis (OP) is a common clinical systemic bone disease, with insidious onset and usually causes serious complications such as fractures. Studies have found that the dysfunction of a variety of bone cells will lead to enhanced bone resorption and reduced bone formation capacity, thus resulting in the imbalance of bone homeostasis and OP disease. As a class of regulatory death mode that affects cell function, programmed cell death (PCD) has been proved to play an important role in maintaining various bone cells growth activities and maintaining bone homeostasis. In addition, several studies have shown that mitochondria are important regulators of a variety of PCD, and various drugs can target mitochondria to regulate the programmed death of bone cells, which is of great significance to further explore the pathogenesis of OP and look for new and efficient drugs for OP.